2020
DOI: 10.1016/j.radi.2019.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for radiographer reporting in Ghana and the potential for improved patient care

Abstract: 2020. Opportunities for radiographer reporting in Ghana and the potential for improved patient care. Radiography 26 (2) , e120-e125.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…In Ghana, radiographer-led reporting is thought to be the professional practice most likely to deliver local patient benefit, and there is evidence that radiographers can report select radiographs as accurately as radiologists. 256 Senior radiographers reporting appendicular skeletal trauma radiographs in a South African hospital achieved higher reporting accuracy and sensitivity than medical officers. 255 Task shifting for breast ultrasound has been initiated as an alternative to mammography in low-resource areas and is considered an appropriate option considering the absence of infrastructure for mammography programmes.…”
Section: Expansion Of the Global Diagnostics Workforce Capacitymentioning
confidence: 93%
“…In Ghana, radiographer-led reporting is thought to be the professional practice most likely to deliver local patient benefit, and there is evidence that radiographers can report select radiographs as accurately as radiologists. 256 Senior radiographers reporting appendicular skeletal trauma radiographs in a South African hospital achieved higher reporting accuracy and sensitivity than medical officers. 255 Task shifting for breast ultrasound has been initiated as an alternative to mammography in low-resource areas and is considered an appropriate option considering the absence of infrastructure for mammography programmes.…”
Section: Expansion Of the Global Diagnostics Workforce Capacitymentioning
confidence: 93%
“…Most of the other regions of the country are faced with limited medical resources including diagnostic medical imaging equipment and infrastructure. 5 However, in line with international guidelines, 7,8 chest imaging is key in the diagnosis and management of COVID-19 in Ghana. Evidence of pulmonary involvement in the pathogenesis of the COVID-19 infection can be detected on both chest X-ray (CXR) and computed tomography (CT), typically, as multifocal, bilateral, peripheral ground-glass opacities and crazy paving consolidations.…”
Section: Introductionmentioning
confidence: 99%
“…Ghana is a democratically stable developing country in West Africa with a population of about 30 million, 5,6 however, the medical system is heavily centred in the major cities including Accra (the capital) and Kumasi, in the centre of the country. Most of the other regions of the country are faced with limited medical resources including diagnostic medical imaging equipment and infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Wuni at al 43 identified opportunities for role extension in radiographer reporting in Ghana, identified the need for the education, training and regulation as critical elements and Atta-Boateng found that Ghanaian radiographers were willing to extend their role into image interpretation. 44 The current study builds on this finding by exploring the role that policy plays in guiding the introduction of role extension in Ghana and identifying areas that such a policy should address.…”
Section: Ghana Introductionmentioning
confidence: 99%